2015
DOI: 10.1051/0004-6361/201425295
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimation of superdiffusive motion of energetic particles upstream of heliospheric shocks

Abstract: Context. In-situ spacecraft observations recently suggested that the transport of energetic particles accelerated at heliospheric shocks can be anomalous, i.e. the mean square displacement can grow non-linearly in time. In particular, a new analysis technique has permitted the study of particle transport properties from energetic particle time profiles upstream of interplanetary shocks. Indeed, the time/spatial power laws of the differential intensity upstream of several shocks are indicative of superdiffusion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 51 publications
1
39
1
Order By: Relevance
“…In the above equation, n is the particle number density, C is a constant, 0 < < 1 and µ = 2 implies subdiffusion, while = 1 and 1 < µ < 2 implies superdiffusion; when fractional derivatives on both time and space are used, the anomalous regimes are characterized by ↵ = 2 /µ (see Zaslavsky 2002;Perrone et al 2013;Bovet et al 2014a;Stern et al 2014, for more details). This relation is different from the one given above for Lévy walks, even for = 1, but it can be shown that the same relation is obtained when the finite extent of the integration domain over x is taken into account (Zumofen & Klafter 1993;Perri et al 2015).…”
Section: Introductioncontrasting
confidence: 55%
See 3 more Smart Citations
“…In the above equation, n is the particle number density, C is a constant, 0 < < 1 and µ = 2 implies subdiffusion, while = 1 and 1 < µ < 2 implies superdiffusion; when fractional derivatives on both time and space are used, the anomalous regimes are characterized by ↵ = 2 /µ (see Zaslavsky 2002;Perrone et al 2013;Bovet et al 2014a;Stern et al 2014, for more details). This relation is different from the one given above for Lévy walks, even for = 1, but it can be shown that the same relation is obtained when the finite extent of the integration domain over x is taken into account (Zumofen & Klafter 1993;Perri et al 2015).…”
Section: Introductioncontrasting
confidence: 55%
“…Litvinenko & Effenberger (2014) verified their results with complementary solution methods using a weak diffusion approximation and a Fourier-series solution on a finite domain (Stern et al 2014). Furthermore, the relation ↵ = 3 µ is recovered for the time dependence of the variance of particle displacement when a finite particle speed is considered (see also the discussion in Perri et al 2015). An additional, complementary solution method for fractional diffusion equations is based on a generalization of the equivalence between stochastic differential equations (SDEs) and the Fokker-Planck equation (Gardiner 2009).…”
Section: Superdi Usive Transport At Heliospheric Shocksmentioning
confidence: 53%
See 2 more Smart Citations
“…Thus, it appears that a power-law intensity decrease upstream is a direct consequence of Alfvén wave excitation by SEPs undergoing DSA at quasi-parallel shocks (see also Afanasiev [19] for a similar discussion). Therefore, at quasiparallel shocks upstream wave excitation provides an alternative explanation for such power laws thought by some to be produced by anomalous diffusion of energetic particles across traveling shocks [24].…”
Section: Simulation Resultsmentioning
confidence: 99%